Performance of tuned mass damper against structural collapse due to near fault earthquakes - Domizio, Martin Norberto (2015)
Tuned mass dampers (TMD) are devices capable of reducing structural vibration by means of transferring energy from the protected structure to the control device. This vibration control strategy has relatively recent use in civil structures, and was proven effective against wind and far-fault earthquakes. In this paper, the effect of near-fault seismic records on structures with TMDs is studied. This type of seismic records has a short significant duration, with few pulses of high amplitude and low frequency. These characteristics raise a question about TMD performance against this type of earthquakes because the device has a very limited time to transfer the energy from the main structure. In this paper, the efficiency of TMD in preventing the collapse of a structure subjected to a series of near-fault records is analyzed. The structure used is a 4-story steel frame on which TMDs with different values of mass are incorporated. From a series of nonlinear dynamic analyses, where the scale of seismic records is modified, the minimum amplitude of each record that produces the structural collapse is found. By comparing the results of the structure with and without the addition of the control device, conclusions about its performance and capability in the prevention of collapse are established.